IDENTIFICATION OF WORK BEHAVIOR GENERATION Z AS A DETERMINING FACTOR FOR WORKSPACE DESIGN - Hanifah
The relationship between space and human being are strongly influenced by the needs, characteristics, and dominant behaviors of human beings, furthermore the idea of a workspace consistently modify followed by the human needs. The change happens through generations or commonly called "regeneration", which is a transitional occasion of human progress. Nowadays, Z generation in the labor market is still in little amounts, yet later Z generation will fill the greater part of the workplaces for these days they still in school and university, therefore companies must be prepared to confront it. The characteristics of generations are different from the typical culture and country. This research aims to present expectations and view of the work behavior of Z generation students in Indonesia that will eventually enter the world of the future work from various groups, remembering that major is one of the ways for most people to prepare themselves for work. And confirm whether the Z generation in Indonesia is the same as other Z generation of other countries that have done by previous researchers, and to find out which indicators are most likely to contribute greatly in the forming factor of the Z generation’s work behavior. Z generation’s behavior is influenced by several significant latent variables, namely intrinsic factors, extrinsic factors, altruistic factors, status-related factors, and social factors. This research used a quantitative methodology. Confirmatory Factor Analysis is used to discover the indicators and latent variables that contributed greatly to work behavior of Z generation. The study as well used a comparative analysis of k independent samples, to determine if the majors played an important role in how Z generation form a work value that can encourage Z generation work behavior in Indonesia. In this study, it was discovered that the forming factor of the Z generation work behavior in Indonesia was the same as that of previous researchers except for the work value of altruistic, the work value of status-related, and the work value of social-related have a big contribution in the forming Z generation work behavior especially in the creative, technological, and business economics fields. The study also find that the choice of majors or fields do not play an important role in how Z generation forms the work value. The results of the study can be a recommendation for a workspace design concept for Z generation especially in the creative, technological, and business economics fields.